Canagliflozin mitigates ferroptosis and improves myocardial oxidative stress in mice with diabetic cardiomyopathy - Du, Shuqin; Shi, Hanqiang; Xiong, Lie; Wang, Ping; Shi, Yanbo (Frontiers in Endocrinology, 2022)
Canagliflozin (Cana), an anti-diabetes drug belongs to sodium-glucose cotransporter 2 inhibitor, is gaining interest because of its extra cardiovascular benefits. Ferroptosis is a new mode of cell death, which can promote the occurrence of diabetic cardiomyopathy (DCM). Whether Cana can alleviate DCM by inhibiting ferroptosis is the focus of this study. Here, we induced DCM models in diabetic C57BL6 mice and treated with Cana. Meanwhile, in order to exclude its hypoglycemic effect, the high glucose model in H9C2 cells were established. In the in vivo study, we observed that Cana could effectively alleviate the damage of cardiac function in DCM mice, including the increasing of lactate dehydrogenase (LDH) and cardiac troponin I (cTnI), the alleviating of myocardial fiber breakage, inflammation, collagen fiber deposition and mitochondrial structural disorder. We evaluated reactive oxygen species (ROS) levels by DCFH-DA and BODIPY 581/591 C11, in vitro Cana reduced ROS and lipid ROS in H9C2 cells induced by high glucose. Meanwhile, JC-1 fluorochrome assay showed that the decreased mitochondrial membrane potential (MMP) was increased by Cana. Furthermore, the inhibitory effects of Cana on myocardial oxidative stress and ferroptosis were verified in vivo and in vitro by protein carbonyl (PCO), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione (GSH). As a key inducer of ferroptosis, the deposition of total iron and Fe2+ can be inhibited by Cana both in vivo and in vitro. In addition, western blot results indicated that the expression of ferritin heavy-chain (FTN-H) was down-regulated, and cystine-glutamate antiporter (xCT) was up-regulated by Cana in DCM mice and cells, suggesting that Cana inhibit ferroptosis by balancing cardiac iron homeostasis and promoting the system Xc-/GSH/GPX4 axis in DCM. These findings underscore the fact that ferroptosis plays an important role in the development and progression of DCM and targeting ferroptosis may be a novel strategy for prevention and treatment. In conclusion, Cana may exert some of its cardiovascular benefits by attenuating ferroptosis.